Experiences of territorial analysis and zoning in order to integrate the development, heritage and landscape policies in land planning (Ciudades, 2017)
We present a series of experiences of territorial analysis for zoning in the context of regional planning. They are based on a methodology that allows the integration of all territorial values and provides an adequate basis for the development of proposals for action in environmental, cultural, economic, social and landscape matters. Appropriate to meet the new legislative and social requirements of regional planning, this methodology is based on the decomposition of space into small territorial units that, taken as a whole, help to understand the behaviour of society with respect to its physical space or living environment and, individually, facilitate the analysis of the characteristics and values of the different parts of the territory.This reflection on regional planning aims to contribute to the renewal of a discipline that, nowadays, should be able to expand its scope overcoming the single-centered approaches (spatial planning, regional development planning, land administration and sectorial policies) and developing new integrative methodologies that facilitate decision making to protect, regulate and manage the heritage values of the territory and landscape, thereby contributing to sustainable development and definition of territorial governance models.
Keywords: territorial analysis; regional planning; territorial units; landscape; territorial heritage; territorial development